Strengthening capacity-building in malaria and schistosomiasis control under China-Africa cooperation: Assessing a case study of Burkina Faso - Hong-Mei Li; Diakourga Arthur Djibougou; Shen-Ning Lu; Shan Lv; Dramane Zongo; Duo-Quan Wang; Wei Ding; Ying-Jun Qian; Lu-Lu Huang; Ya-Yi Guan; Ning Xiao; Potiandi Serge Diagbouga; et al. (Science in One Health, 2022)
Malaria and schistosomiasis are highly prevalent in Burkina Faso, whereas China has successfully eliminated malaria as well as schistosomiasis as a public health problem. To implement the China-Africa health cooperation initiative, a series of activities were launched since 2019 to enhance understanding and cooperation among malaria and schistosomiasis professionals in China and Burkina Faso. This study described the achievements of the First Virtual Symposium of China-Burkina Faso Cooperation on Schistosomiasis and Malaria Control. Pre- and post-test questionnaires were employed to study the knowledge changes of participants regarding malaria and schistosomiasis control and elimination, explore capacity-building priorities, and identify potential challenges. Chi-squared statistics were used to compare the differences between sub-groups, and p value < 0.05 was considered statistically significant. Participants ranked their preferences for challenges and capacity-building priorities in future cooperation. The responses of participants from both China and Burkina Faso indicated effective improvement in their general knowledge about the diseases whereas the improvement in professional knowledge on malaria and schistosomiasis was limited. The total correct response rate increased from 54.08% to 66.78%. Chinese participants had better schistosomiasis knowledge than Burkina Faso participants did, but the same result was not found for malaria. Diseases control strategies, surveillance and response system, and diagnostics techniques were identified as the top three priorities for future capacity building. Participants from China and Burkina Faso shared almost the same views about challenges except with respect to pathogens, which the former saw as a major challenge and the latter did not. The study findings will help policymakers, health managers, and researchers to understand the future cooperation between Burkina Faso and China on malaria and schistosomiasis.